2016
DOI: 10.18632/oncotarget.8779
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong challenge of calcium homeostasis in male mice lacking TRPV5 leads to changes in bone and calcium metabolism

Abstract: Trpv5 plays an important role in calcium (Ca2+) homeostasis, among others by mediating renal calcium reabsorption. Accordingly, Trpv5 deficiency strongly stresses Ca2+ homeostasis in order to maintain stable serum Ca2+. We addressed the impact of lifelong challenge of calcium homeostasis on the bone phenotype of these mice.Aging significantly increased serum 1,25(OH)2D3 and PTH levels in both genotypes but they were more elevated in Trpv5−/− mice, whereas serum Ca2+ was not affected by age or genotype. Age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This means that bone loss should be attributed to 1,25(OH) 2 D 3 , rather than TRPV5 deletion, in vivo. Especially, in long-term bred TRPV5-deficient mice, old TRPV5-deficient mice bone resorption function was found to be essentially the same as that of wild mice, which is attributed to over expression of 1,25(OH) 2 D 3 in old mice compared to young ones (58). In short, this evidence has confirmed that TRPV5 promotes bone resorption in wild type mice (57,58,60,61).…”
Section: Trpvmentioning
confidence: 60%
See 3 more Smart Citations
“…This means that bone loss should be attributed to 1,25(OH) 2 D 3 , rather than TRPV5 deletion, in vivo. Especially, in long-term bred TRPV5-deficient mice, old TRPV5-deficient mice bone resorption function was found to be essentially the same as that of wild mice, which is attributed to over expression of 1,25(OH) 2 D 3 in old mice compared to young ones (58). In short, this evidence has confirmed that TRPV5 promotes bone resorption in wild type mice (57,58,60,61).…”
Section: Trpvmentioning
confidence: 60%
“…However, the effects of TRPV5 on bone resorption by osteoclasts have not been conclusively determined. TRPV5-deficient mice showed gross phenotypic dysregulation of Ca 2+ homeostasis, severe hypercalciuria and excess bone loss in the musculoskeletal system (57)(58)(59). Interestingly, bone resorption was significantly inhibited in in vitro cell cultures from TRPV5-deficient mice (57,58,60).…”
Section: Trpvmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that TRPV5 may be an important pathway, mediating RANKL-induced [Ca 2+ ] i elevation in osteoclasts. A role for TRPV5 in osteoclast calcium homeostasis was also confirmed [ 128 ]. Interestingly, studies have shown that estrogen inhibits RANKL-induced osteoclast differentiation and bone resorption activity by increasing the expression of TRPV5 channels [ 129 ].…”
Section: Transient Receptor Potential (Trp) Channelsmentioning
confidence: 93%